2016
DOI: 10.3892/br.2016.622
|View full text |Cite
|
Sign up to set email alerts
|

Soluble cluster of differentiation 36 concentrations are not associated with cardiovascular risk factors in middle-aged subjects

Abstract: Abstract. Cluster of differentiation 36 (CD36) is involved in the development of atherosclerosis by enhancing macrophage endocytosis of oxidized low-density lipoproteins and foam cell formation. Soluble CD36 (sCD36) was found to be elevated in type 2 diabetic patients and possibly acted as a marker of insulin resistance and atherosclerosis. In young subjects, sCD36 was associated with cardiovascular risk factors including obesity and hypertriglyceridemia. The present study was conducted to further investigate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 35 publications
2
12
0
Order By: Relevance
“…Several studies have demonstrated up regulation of sCD36 in certain diseases. 23,24,26,27 In conclusion, we showed that CD36 Type I deficiency exists in Thais. These individuals are at risk of developing anti-CD36s, which are responsible for the development of bleeding disorders such as PTR and FNAIT in our population.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Several studies have demonstrated up regulation of sCD36 in certain diseases. 23,24,26,27 In conclusion, we showed that CD36 Type I deficiency exists in Thais. These individuals are at risk of developing anti-CD36s, which are responsible for the development of bleeding disorders such as PTR and FNAIT in our population.…”
Section: Discussionmentioning
confidence: 59%
“…This variability may be caused by factors including the origin (plasma or serum), handling (preparation, storage) of the blood samples, and by other specific factors such as different mutations. Several studies have demonstrated up regulation of sCD36 in certain diseases …”
Section: Discussionmentioning
confidence: 99%
“…Many investigators have shown an association of sCD36 with components of the metabolic syndrome, such as insulin resistance and central obesity [ 69 , 75 , 76 , 77 ], which are key predictors of T2DM and risk factors of accelerated atherosclerosis in this group of patients. However, there was a study on the middle-aged patient population with T2DM from Jordan, in which no difference in sCD36 levels was found between patients with metabolic syndrome and healthy controls [ 78 ]. The association with the risk of T2DM has also been described, but it was not independent of fasting glucose, insulin, or adiposity [ 76 , 79 ].…”
Section: Association Of Scd36 With Diabetes Mellitusmentioning
confidence: 99%
“…176 Several studies have analysed sCD36 levels in plasma samples; however, these samples have to potential to skew interpretation of the results owing to the presence of CD36 in platelets, which could represent a marker of platelet activation. 177,184,185 Furthermore, microparticles that are released upon platelet activation might represent an important source of CD36.…”
Section: [H1] Soluble Cd36 -A Potential Biomarkermentioning
confidence: 99%